Tourism Management Issues and its Relationship with the Sustainable Development Goals - Vidya Imanuari Pertiwi; Bagus Nuari Harmawan (Pusjar SKPP Lembaga Administrasi Negara, 2022)
The development of tourism looks brilliant because of the achievement of its economic contribution. However, current tourism management, especially in Indonesia, tends to neglect the ecological aspects of the environment and the social community. This injures Indonesia's commitment to sustainable development. This study aims to review the development of tourism in Indonesia and the impact caused by tourism development, especially tourism development in Yogyakarta. The methodology used in this study is qualitative by using secondary data such as journal articles, news, books, and government report. The study results found that tourism development in Indonesia, especially in Yogyakarta Province, only focuses on the economic sector. The tourism sector management actors focus more on making as much profit as possible without paying attention to sustainable tourism development. This results in environmental problems such as the scarcity of clean water for the community. Tourism management that does not pay attention to sustainable tourism practices also causes community conflicts against tourism actors